The use of modification structures as a measure of language growth among students of Quirino High School, Quezon City - De Leon, Lydia Bundoc 1933- ([Quezon City s.n.], 1967)
This study determined the use of modification structures in composition writing among students in the eleven public high schools of Quezon City as a measure of language growth. The relationship that exists between the increase in the curricular year level and the increase in the use of modification structures using quantitative methods was investigated.
Thesis (M.A.T.English)--University of the Philippines
Keywords: English language -- Sentences; English language -- Composition and exercises